2021
DOI: 10.3390/pharmaceutics13070952
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluations of Modified Rice Hydrogel for Topical Ophthalmic Drug Delivery of Praziquantel on Avian Philophalmiasis

Abstract: The present study aims to evaluate the efficacy of a novel drug delivery system of the modified rice hydrogel containing praziquantel (PZQ) against Philophthalmus gralli isolated from ostrich eyes and determine the toxicity of the preparation on chicken eye model. The parasiticidal activity of PZQ (0, 1, 10, and 100 µg/mL) was tested on P. gralli. The ophthalmic antiparasitic hydrogel was formulated with appropriate amount of PZQ and chemically modified rice gel. The parasitic morphology after exposure with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…Similarly, we were unable to confirm the promising in vitro data reported for praziquantel in the treatment of the closely related P. gralli [ 18 ]. In our in vivo trial, we did not observe any effect of praziquantel when administered in combination with milbemycin (Table 2 ).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Similarly, we were unable to confirm the promising in vitro data reported for praziquantel in the treatment of the closely related P. gralli [ 18 ]. In our in vivo trial, we did not observe any effect of praziquantel when administered in combination with milbemycin (Table 2 ).…”
Section: Discussioncontrasting
confidence: 86%
“…In our in vivo trial, we did not observe any effect of praziquantel when administered in combination with milbemycin (Table 2 ). Praziquantel is toxic to Philophthalmus in vitro [ 18 ]. However, in a previous study it was found to be ineffective when used for 3 consecutive days in multitherapy with pyrantel and fenbendazole in vivo [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been previously reported by many researchers when testing the in vitro effect, eg. PZQ (Kato et al, 2013;Prompetch et al, 2021), seeds of J. curcas (Kandil et al, 2018), seeds of M. oleifera (Eguale & Giday, 2009) on Schistosoma mansoni, Philophthalmus gralli, Haemonchus contortus, Fasciola hepatica, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Also, has been found Venezuela (Diaz et al, 2002), Brazil (Verocai et al, 2009) and in Zimbabwe (Mukaratirwa et al, 2005) In general a variety of mammals, including humans, occasionally serve as the intermediate as well as the definitive hosts for the genus Philophathalamus. Moreover, the zoonotic philophthalmiasis in human cases has been also documented in various parts of the world (Sapp et al, 2019 andPrompetch et al, 2021). Lang et al, 1993;Kanev et al, 1993 &Kanev, 1995 reported cases of human infection and conjunctivitis in eyes due to infection with P. palpebrarum; P. lucipetus and P. lachrymosus, respectively.…”
Section: Philophthalamus Palpebrarum;mentioning
confidence: 99%